Thermally Induced Dehydrogenation of Amine–Borane Adducts and Ammonia–Borane by Group 6 Cyclopentadienyl Complexes Having Single and Triple Metal–Metal Bonds. Issue 28 (9th August 2013) - García‐Vivó, Daniel; Huergo, Estefanía; Ruiz, Miguel A.; Travieso‐Puente, Raquel
Abstract: Treatment of solutions of ammonia–borane (NH3 · BH3, AB) with catalytic amounts (5 mol‐%) of the singly bonded dimers [M2 Cp2 (CO)6 ] [M = Cr (1a ), Mo (1b ), W (1c ); Cp = cyclopentadienyl] under mild thermal activation (333 K) led to the progressive dehydrogenation of the adduct and quantitative conversions were achieved after 12, 24, and >34 h, respectively. At the initial stages of these reactions (low conversions), the major products were cyclic and branched oligomers of aminoborane (NH2 =BH2 ). However, at longer reaction times (high conversions), the major products were, in all cases, borazine, [HNBH]3, and polyborazylene, [NBH x ] ( x  < 1), whereas other minor products were derived from B–N bond‐cleavage processes. Over the course of these reactions, complexes1a –c were transformed into the corresponding mononuclear hydrides [MCpH(CO)3 ] [M = Cr (2a ), Mo (2b ), W (2c )], which are supposed to be the catalytically active species in these processes, as also supported by similar catalytic activity exhibited by pure samples of the dihydride [Mo2 Cp2 (H)2 (μ‐Ph2 PCH2 PPh2 )(CO)2 ] (2b′ ). Under similar conditions, 1a –c were also active catalysts for the dehydrogenation of adducts derived from substituted amines ( t BuH2 N· BH3 and Me2 HN· BH3 ), although the rate of dehydrogenation was significantly lower than that of AB. This lower activity follows from deprotonation of hydrides2 by the free amines, which are in turn generated through B–N bond‐cleavage processes. The dehydrogenation products of t BuH2 N· BH3 are also derived from oligomerization processes of the corresponding aminoborane ( t BuHN=BH2 ), which in this case was identified in the reaction mixtures, but even at long reaction times, the formation of the borazine‐like product was not complete, and the reaction mixture contained significant amounts of (poorly defined) soluble polymeric materials. For Me2 HN· BH3, the major product obtained in all of the reactions was cyclic dimer [Me2 N=BH2 ]2 . Similar studies were performed with triply bonded complexes [Mo2 Cp2 (CO)4 ] (3b ) and [Mo2 Cp2 (μ‐Ph2 PCH2 PPh2 )(CO)2 ] (3b′ ), which displayed similar catalytic activity while remaining essentially unperturbed along the reactions, and these complexes yielded product distributions that were similar to those observed for singly bonded dimers1a –c . Abstract : Readily accessible group 6 binuclear cyclopentadienyl complexes having single and triple M–M bonds are efficient catalysts for the dehydrogenation of a range of amine–borane adducts, including ammonia–borane, under mild thermal activation (333 K).